Intelligent manufacturing and mechatronics : proceedings of the 2nd Symposium on Intelligent Manufacturing and Mechatronics - SympoSIMM 2019, 8 July 2019, Melaka, Malaysia /: proceedings of the 2nd Symposium on Intelligent Manufacturing and Mechatronics - SympoSIMM 2019, 8 July 2019, Melaka, Malaysia. ([2020]) - Unknown
No abstract available